H syndrome treated with Tocilizumab: two case reports and literature review - Jacquot, Robin; Jouret, Maurine; Valentin, Mathieu Gerfaud; Richard, Maël; Jamilloux, Yvan; Rousset, Florent; Emile, Jean-François; Haroche, Julien; Steinmüller, Lars; Zekre, Franck; Phan, Alice; Belot, Alexandre; et al. (Frontiers in Immunology, 2023)
H syndrome is a rare autosomal recessive genetic disorder characterized by the following clinical features: cutaneous hyperpigmentation, hypertrichosis, hepatosplenomegaly, heart anomalies, hearing loss, hypogonadism, short stature, hallux valgus, hyperglycemia, fixed flexion contractures of the toe joints and the proximal interphalangeal joints. In rare cases, autoinflammatory and lymphoproliferative manifestations have been also reported. This disorder is due to loss-of-function mutations in SLC29A3 gene which encode the equilibrative nucleoside transporter ENT3. This deficiency leads to abnormal function and proliferation of histiocytes. H syndrome is part of the R- group of histiocytosis. We report two different cases, one was diagnosed in adulthood and the other in childhood. The first case reported is a 37-year-old female suffering from H syndrome with an autoinflammatory systemic disease that begins in adulthood (fever and diffuse organ’s infiltration) and with cutaneous, articular, auditory and endocrinological manifestations since childhood. The second case reported is a 2-year-old girl with autoinflammatory, endocrine and cutaneous symptoms (fever, lymphadenopathy, organomegaly, growth delay and cutaneous hyperpigmentation). Homozygous mutations in SLC29A3 confirmed the diagnosis of H syndrome in both cases. Each patient was treated with Tocilizumab with a significant improvement for lymphoproliferative, autoinflammatory and cutaneous manifestations. Both cases were reported to show the multiple characteristics of this rare syndrome, that can be diagnosed either in childhood or in adulthood. In addition, an overview of the literature suggested Tocilizumab efficiency.